ARCHITECTURE OF THE XXI CENTURY: INNOVATIONS AND NEW TRENDS (Journal of Universal Science Research, 2025)
modern architecture has undergone tremendous changes in the 21st century. As a result of new technologies, environmental demands and social needs, architecture has taken a more functional, energy efficient and aesthetically developed direction. Today, innovation, technology and environmental sustainability have become fundamental principles of architecture. One of the main aspects of modern architecture is the application of smart technologies. Smart buildings are controlled through artificial intelligence, automated control systems, and sensory systems. As a result of automation of lighting, heating, cooling and safety systems, energy efficiency is increased and comfortable living conditions are created. Also, these technologies help to reduce the environmental impact while simplifying human life.